Stereotactic body radiation therapy for an octogenarian with pulmonary carcinosarcoma - Huang, Wei‐Lun (Thorac Cancer, 2021)
Pulmonary carcinosarcoma is a rare lung tumor accounting for <1% of primary lung cancers, characterized by biphasic components with both carcinomatous and sarcomatous mesenchymal features. This report describes a case of pulmonary carcinosarcoma in an octogenarian who was treated with stereotactic body radiation therapy (SBRT) and whose therapeutic response was sustained for 2 years. Along with other treatment modalities, SBRT might be considered for the treatment of medically inoperable localized stage pulmonary carcinosarcoma.